2013
DOI: 10.1007/s00441-013-1743-2
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Shox2 with human SHOX leads to congenital disc degeneration of the temporomandibular joint in mice

Abstract: The temporomandibular joint (TMJ) consists of the glenoid fossa arising from the otic capsule through intramembranous ossification, the fibrocartilaginous disc and the condyle, derived from the secondary cartilage by endochondral ossification. We have reported previously that cranial neural crest-specific inactivation of the homeobox gene Shox2, which is expressed in the mesenchymal cells of maxilla-mandibular junction and later in the progenitor cells and perichondrium of the developing chondyle, led to dyspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 51 publications
5
30
0
Order By: Relevance
“…Results demonstrated that the number of apoptotic cells increased dramatically in the SHOX2 silencing group compared to control, suggesting that SHOX2 was involved in the regualtion of NP cell apoptosis. This is similar to a previous study, which found that the number of apoptotic cells increased dramatically in articular disc of SHOX2 SHOX‐KI/KI TMJ …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Results demonstrated that the number of apoptotic cells increased dramatically in the SHOX2 silencing group compared to control, suggesting that SHOX2 was involved in the regualtion of NP cell apoptosis. This is similar to a previous study, which found that the number of apoptotic cells increased dramatically in articular disc of SHOX2 SHOX‐KI/KI TMJ …”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that pMes‐stop SHOX2 in TMJ resulted in reduction of Col I, Col II, AGG, and Gli2, along with increased cell apoptosis, as well as enhanced MMPs (MMP9 and MMP13) activity in the condyle . Li et al also reported that the expression of collagen I decreased in the SHOX2 SHOX‐KI/KI TMJ disc, aggrecan decreased in the disc and condoyle of SHOX2 SHOX‐KI/KI TMJ. Furthermore, they found that MMP9 and MMP13 expression was enhanced in the articular disc of SHOX2 SHOX‐KI/KI TMJ.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A number of transcription factors and growth factors have been reported with regard to their essential roles in TMJ morphogenesis and growth, such as Runx2, Sox9, Shox2, Spry1 and Spry2, Bmpr1A, Tgfbr2, and Ndst1 (Shibata et al 2004; Fukuoka et al 2007; Mori-Akiyama et al 2003; Wang et al 2011; Gu et al 2008, 2014; Li et al 2014; Purcell et al 2012; Oka et al 2007; Yasuda et al 2010). Among them, Indian hedgehog (Ihh), a signaling molecule that plays a pivotal role in the regulation of chondrocyte proliferation, maturation, and ossification both in long-bone development and digit joint formation (St-Jacques et al 1999), has also been found to be essential for TMJ development (Shibukawa et al 2007; Purcell et al 2009; Gu et al 2014).…”
Section: Introductionmentioning
confidence: 99%